Rekonstruksi Kepemimpinan Gereja dari Paradigma Sarkikos menuju Pneumatikos: Analisis Teologis 1 Korintus 3:1–9 - Victorius Soebagio; Yanto Paulus Hermanto (KAPATA: Jurnal Teologi dan Pendidikan Kristen, 2026)
The issue of spiritual immaturity remains a persistent challenge within contemporary Christian communities, often manifested through divisions, leadership cults, and dependency on charismatic leaders. This study explores Paul’s teaching in 1 Corinthians 3:1–9 as a theological foundation for reconstructing church leadership from a sarkikos (fleshly) orientation toward a pneumatikos (spiritual) paradigm. Using a qualitative biblical-theological approach combined with contextual analysis of the Corinthian socio-cultural setting, this research examines Paul's critique of factionalism and his theology of ministry collaboration. The findings reveal that Paul reframes leadership as participatory service within God’s mission rather than hierarchical authority centered on personal charisma. The study contributes to contemporary ecclesiology by proposing a reconstructive leadership model rooted in spiritual maturity, collaborative ministry, and Christ-centered formation. Such a paradigm challenges modern churches to move beyond personality-driven leadership toward a spiritually formative community.